Effect of macrophyte vermicompost on growth and productivity of brinjal (Solanum melongena) under field conditions - Ishtiyaq Ahmed Najar; Anisa B. Khan; Abdul Hai (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Background Macrophytes (fresh water plants) comprise a diverse group of the flora which play important roles in the maintenance of trophic food chains and biogeochemical processes, but are deleterious when present in excess. However, due to various anthropogenic activities, there is accumulation of nutrients in aquatic ecosystems resulting in massive macrophytic growth. These weeds do not possess any economic value and remain laid on lake shores after harvesting and become a source of odor problem, thus posing a challenge to the lake management authorities regarding their proper disposal. However, vermicomposting turns these macrophytes into materials useful in horticulture/agriculture for restoration of soil fertility, in addition to providing a solution to the nuisance of harvested weeds. Results The study was conducted to investigate the effect of different rates (2, 4 and 6 t/ha) of macrophyte-based vermicompost on germination, growth and yield of Solanum melongena under field conditions. The data revealed that different rates of vermicompost produced varied and significant effect (P.05) as compared to the control on germination, growth and yield parameters with maximum value recorded at 6 t/ha, followed by 4 t/ha and the least at 2 t/ha. The dose of 6 t/ha significantly (P.05) increased germination (22.56 ± 2.5 %), number of fruits per plant (3.55 ± 0.07) mean fruit weight (73 ± 5.0 g), yield per plant (1.48 ± 0.05 kg) and marketable fruits (28.66 ± 3.0 %) when compared with the control. The study suggests that macrophyte-based vermicompost as a potential source of plant nutrients for sustainable crop production. Conclusion Macrophyte-based vermicompost is an efficient quality yielder and economy enhancer for sustainable agriculture especially for the communities having vegetable gardens around lakes will benefit by using macrophyte vermicompost, a balanced and low-cost organic fertilizer.